The relationship between leaf area and vegetative characteristics in Barecat and French faba bean cultivars - Mohammadkazem Eslami; Ebrahim Zeinali; Afshin Soltani; Mohammad Khadempir (پژوهش‌های حبوبات ایران, 2018)
Introduction Since the leaves are the main source of production of photosynthetic substances in plants, dry matter production and crop yield potential is largely depend on the leaf surface, and many environmental changes affect growth and yield through changes in leaf area. Hence, green leaf area per plant and leaf area index measure in almost all studies of crop physiology to understand the mechanism of yield alteration. However, measurement of leaf area compared with other traits such as plant height and total plant dry weight is very difficult, precise instruments and spend more time and cost. Therefore, according to the allometric relationships in plants, extensive studies were done to find the relationship between leaf area and other plant traits that their measurement is easier, faster and cheaper, and does not require expensive equipment. Allometric relationships in plants reveal changes in the growth of an organ of plant than to all or another part or organ of plant. The leaf area in plant as main source of photosynthetic substances closely associated with the growth and yield. Thus, it is usually measured for justifying variations of the growth and yield. Due to the difficulty, time‌consuming and requires devices to measure leaf area, an alternative approach for measuring the leaf area is the use of allometric relationships between leaf area and traits that their measuring is easy and quick and requires no expensive equipment. This study aimed to obtain the allometric relationships between green leaf area and a number of vegetative attributes such as number of leaves per main stem, green leaf dry weight, total dry weight of vegetative parts of plant. Allometric equations was used successfully to calculate leaf area in various crops such as cotton, wheat, chickpea, faba bean, peanuts, soybean and sweet sorghum. The effects of three factors cultivar, inter‌ and intra‌row spacing on the allometric relationships were examined.